Level of Scientific Literacy in Junior High School Students: Survey Research Based on Grade Level - Silitonga, Rotua Fetricia (Universitas Negeri Semarang, 2025)
This research aimed to investigate the level of scientific literacy among junior high school students. The study used a quantitative approach with a survey design. A total of 152 participants, consisting of 90 female and 62 male students, were involved in the study conducted in Bandung City and Pekanbaru City. The instruments used in the research were adapted from the Scientific Literacy Test (SLT) and an open-ended question. Data analysis involved statistical tests supported by students' responses to the open-ended questions. The findings revealed that junior high school students' average scientific literacy level was 23.46, equivalent to 57.22% of the total SLT score, categorizing it as moderate. The average scientific literacy scores for students in grade 7, 8, and 9 were 23.00, 23.78, and 23.97, respectively. Statistical tests indicated no significant difference in junior high school students' average scientific literacy score (p =0.597). The research noted lower scores on the Nature of Science (NOS) subscale (49.36%) compared to Scientific Concept Knowledge (SCK) subscale (67.30%). This highlights the need to enhance scientific literacy, particularly in NOS aspects, and suggests further investigation into factors influencing junior high school students' scientific literacy.